2020
DOI: 10.1111/apt.16182
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: the effects of immunomodulator or biological withdrawal from mono‐ or combination therapy in inflammatory bowel disease

Abstract: SummaryBackgroundWithdrawal of treatment is a common therapeutic problem in patients with long‐standing remission of inflammatory bowel disease.AimsTo evaluate the relapse rate in patients with quiescent inflammatory bowel disease after cessation of biologic or immunomodulator therapy.MethodsWe searched five databases for studies evaluating disease relapse after withdrawal of monotherapy or a drug from combination therapy in Crohn's disease or ulcerative colitis. In meta‐analysis, risk ratios (RR) were calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 74 publications
(343 reference statements)
0
4
0
1
Order By: Relevance
“…И здесь не более 29% (42). Что же касается частоты достижения безлекарственной ремиссии, то во временном лаге 8-10 лет это всего лишь 5-10% (9,14). И остро стоят вопросы безопасности, как тематика отдельного и большого разговора.…”
Section: современная терапияunclassified
“…И здесь не более 29% (42). Что же касается частоты достижения безлекарственной ремиссии, то во временном лаге 8-10 лет это всего лишь 5-10% (9,14). И остро стоят вопросы безопасности, как тематика отдельного и большого разговора.…”
Section: современная терапияunclassified
“…The discontinuation of immunomodulator monotherapy is evidently associated with an increased risk of relapse. In a systematic review and meta-analysis encompassing ten randomized controlled trials with 587 included patients, Dohos et al [ 46 ] concluded that continued immunomodulator monotherapy should remain the preferred approach among patients with CD, despite concerns about long-term toxicity. However, the withdrawal of immunomodulator monotherapy did not exhibit a significantly higher risk of relapse within 24 months of follow-up in UC (RR = 1.39, 95%CI: 0.85-2.26, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…However, the withdrawal of immunomodulator monotherapy did not exhibit a significantly higher risk of relapse within 24 months of follow-up in UC (RR = 1.39, 95%CI: 0.85-2.26, respectively). Moreover, discontinuing an immunomodulator in combination with biologics did not demonstrate a higher risk of relapse compared to continuing both drugs (RR = 1.30, 95%CI: 0.81-2.08)[ 46 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the forced discontinuation, the intermittent use of biologics is common in Taiwan. After discontinuation of biologics, the major concerns are disease relapse leading to poor outcomes and the requiring of retreatment with biologics 7 . Some studies have investigated the long‐term clinical outcomes after biologics discontinuation and showed that 23–30% of patients with IBD have a relapse within 1 year 8,9 .…”
mentioning
confidence: 99%